We're the Same… but Different: Addressing Academic Divides in the Study of Brain and Behavior - Donaldson, Zoe R. (Frontiers in Behavioral Neuroscience, 2010)
How the brain mediates behavior is a question relevant to a broad range of disciplines including evolutionary biology, basic neuroscience, psychiatry, and population health. Experiments in animals have traditionally used two distinct approaches to explore brain–behavior relationships; one uses naturally existing behavioral models while the other focuses on the creation and investigation of medically oriented models using existing laboratory-amenable organisms. Scientists using the first approach are often referred to and self identify as “neuroethologists,” while the second category spans a variety of other sub-disciplines but is often referred to broadly as “behavioral neuroscience.” Despite an overall common scientific goal – the elucidation of the neural basis of behavior – members of these two groups often come from different scientific lineages, seek different sources of funding, and make their homes in different departments or colleges. The separation of these groups is also fostered by their attendance at different scientific conferences and publication records that reflect different journal preferences. Bridging this divide represents an opportunity to explore previously unanswerable questions and foster rapid scientific advances. This article explores the reasons for this divide and proposes measures that could help increase technology transfer and communication between these groups, potentially overcoming both physical and ideological gaps.